Studies conducted on entrepreneurship in science education: Thematic review of research - Deveci, İsa and Çepni, Salih (Journal of Turkish Science Education, 2017)
In recent years in many educational curriculums, entrepreneurship has attracted much attention as a concept, from primary education to higher education. In this sense, attention is given to the concept of entrepreneurship that is included in both national and international science education curriculums. In this research, the aim was to investigate studies conducted on entrepreneurship in science education in terms of their general characteristics (publication year, number of authors, publication type) and characteristics of their content (purpose, method, data collection tool, sample type, conclusion and suggestions). As a result of the research, it is noteworthy that studies have been published in recent years in general. On the other hand, it was identified that there are studies much more published as literature review, document analysis, theoretical. In some research, it was seen that the teaching model, curriculum and modules are developed and integrated within science education to promote entrepreneurship. In addition, it is observed that in most of the studies have been reached positive results about the concept of entrepreneurship should be integrated with science education. Depending on the results, it should be said that teaching curriculums can be designed and implemented that are likely to improve students’ entrepreneurial skills in science courses.